Prácticas de enseñanza de lógica matemática en educación inicial en el Centro de Educación Inicial de la Cuna a la Luna Pachacamac - Campaña Zambrano, Nora Alejandra (2016)
The study in these pages was conducted to reveal how they conceive and materialize daily teaching practices logical-mathematical at the Center for Early Education "From the cradle to the moon (Pachacamac)", with children of Initial 2. Towards fulfilling that ultimate goal, research was carried out from a qualitative approach and under the descriptive type. Access to the field covered a month: May-June 2015. At preferred a case study, a semi-structured interview and direct observation techniques was used. Thus, it also managed to fulfill the specific objectives: to examine the theoretical and methodological assumptions on which the above teaching practices are based; analyze how these the permeate and/or modify; and describe, from there, processes, phases, tasks, activities, actions, knowledge and other related elements. In this regard, the main results excelled the teacher turned-analysis unit does not comply to the letter the planning that takes place daily, and prioritises other areas at the expense of logical-mathematical relationships.